(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
This study was conducted to determine the seasonal variation of Cr, Ni, Cu, Zn, As, Cd and Pb concentrations in water from four coastal sites of Bangladesh. The mean concentrations of trace metals in the water samples in the range of each elements were Cr (2.6−15.3), Ni (5.1−77.5), Cu (10.2−510), Zn (5.0-1390), As (2.1−13.3), Cd (0.006−0.09), Pb (0.4−109 μg/l) in summer and Cr (3.6−43.7), Ni (10.8−42.4), Cu (7.3−45.2), Zn (18.0-73.9), As (4.0−19.7), Cd (0.025−0.087), Pb (2.8−34.8 μg/l) in winter. The mean concentrations of the metals in water followed a decreasing order of Zn > Cu > Pb > Ni > Cr > As > Cd in the summer and Zn > Ni > Cr > Cu >Pb > As > Cd in the winter. The water of Cox’s Bazar hatchery site showed the highest levels of Zn (1390), Cu (510) and Pb (109 μg/l) in summer while As (19.7 μg/l) showed highest in Cox’s Bazar Bakkhali estuary in the winter samples. The elevated level of Ni (77.5 μg/L) in the summer and Cr (43.7 μg/l) in the winter water samples were also found in the Sundarbans site. The mean concentrations of all estimated trace metals were higher in the winter than in the summer season. It was both in the Chittagong port and Meghna estuary. For the Meghna estuary, the highest concentration of Zn (36.0 μg/l) was observed in the water sample of winter season. Some trace metals exceeded the international quality guidelines. Suspended solid, temperature, rainfall, anthropogenic inputs and geomorphologic setup are influenced by seasonal vagaries which alter the variation of metal distribution. J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(2): 67-80